Laboratorio de Formas de Galicia: Reconstructing the regional identity through architecture - Río Vázquez, Antonio (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2014)
Laboratorio de Formas de Galicia is an interdisciplinary project led by Luis Seoane and Isaac Diaz Pardo from the Argentine exile in mid-twentieth century, with the aim of reconstructing the galician identity and memory from the study and dissemination of existing forms in history and tradition. Recovering the ceramic industry created by Antonio Raimundo Ibáñez in Sargadelos (Lugo) in the early nineteenth century is fixed among its action lines. The factories of Magdalena (Argentina) and the new industrial complex in Sargadelos are create at the end of the sixties with this intention. In its architecture, designed by Andrés Fernández-Albalat in collaboration with Diaz Pardo, new paths about the industrial building are linked to the idea of “new regionalism”, with a careful reading of the site and an attempt to humanize and signify the space of workers. The Laboratorio understand the forms as a wide territory from industrial design to the urban setting. Within this territory, the principles of modernity evolve into a recovery of regional identity. According is defended by their creators, a work must be a child of its time but must not ignore where it comes from.
Keywords: Architecture; XX Century; Galicia; Sargadelos; industry; regionalism